On damping created by heterogeneous yielding in the numerical analysis of nonlinear reinforced concrete frame elements. (1st July 2015) - Jehel, Pierre; Cottereau, Régis
Highlights: A multi-scale stochastic uniaxial cyclic nonlinear concrete model is presented. Elasto-plastic response with heterogeneous yielding is assumed at meso-scale. Heterogeneity is conveyed by the fluctuations of a random field. Response at macro-scale can be independent of the stochastic meso-structure. The developed concrete model can solely generate structural damping. Abstract: In the dynamic analysis of structural engineering systems, it is common practice to introduce damping models to reproduce experimentally observed features. These models, for instance Rayleigh damping, account for the damping sources in the system altogether and often lack physical basis. We report on an alternative path for reproducing damping coming from material nonlinear response through the consideration of the heterogeneous character of material mechanical properties. The parameterization of that heterogeneity is performed through a stochastic model. It is shown that such a variability creates the patterns in the concrete cyclic response that are classically regarded as source of damping.